2016
DOI: 10.7554/elife.13063
|View full text |Cite
|
Sign up to set email alerts
|

α8β1 integrin regulates nutrient absorption through an Mfge8-PTEN dependent mechanism

Abstract: Coordinated gastrointestinal smooth muscle contraction is critical for proper nutrient absorption and is altered in a number of medical disorders. In this work, we demonstrate a critical role for the RGD-binding integrin α8β1 in promoting nutrient absorption through regulation of gastrointestinal motility. Smooth muscle-specific deletion and antibody blockade of α8 in mice result in enhanced gastric antral smooth muscle contraction, more rapid gastric emptying, and more rapid transit of food through the small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…In vascular smooth muscle cells (31,32) and intestinal epithelial cells, knockdown of a8 leads to less active RhoA. In contrast to this scenario, a8b1 ligation in gastric smooth muscle prevents RhoA activation (6). Similar to gastric smooth muscle, we found that a8b1 ligation in ASM prevents RhoA activation and contraction.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…In vascular smooth muscle cells (31,32) and intestinal epithelial cells, knockdown of a8 leads to less active RhoA. In contrast to this scenario, a8b1 ligation in gastric smooth muscle prevents RhoA activation (6). Similar to gastric smooth muscle, we found that a8b1 ligation in ASM prevents RhoA activation and contraction.…”
Section: Discussionmentioning
confidence: 51%
“…Mice with smooth muscle-specific deletion of a8b1 integrin have enhanced force of tracheal smooth muscle contraction in response to IL-13, and Mfge8 binding to a8b1 integrin is essential to abrogate the enhanced contraction. Previous studies have identified the role of a8 in vascular and gastric smooth muscle as well as in intestinal epithelial cells (6,13,31). However, the role of a8b1 in RhoA regulation differs among these cell types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations